Pulmonary Endarterectomy in a Patient with Immune Thrombocytopenic Purpura - YILDIZELİ, BEDRETTİN; ATAGÜNDÜZ, IŞIK (My University, 2015)
Immune thrombocytopenic purpura (ITP) patients are at high risk for bleeding complications regarding surgeries involving cardiopulmonary bypass. We report an ITP patient with chronic thromboembolic pulmonary hypertension who underwent uncomplicated pulmonary endarterectomy with receiving postoperative intravenous immunoglobulin (IVIG) therapy. The positive outcome of this case may suggest that pulmonary endarterectomy surgery is performed safely for ITP patients.